The general and Julia : a novel - Clinch, Jon (Atria Books, 2023)
Barely able to walk and rendered mute by the cancer metastasizing in his throat, Ulysses S. Grant is scratching out words, hour after hour, day after day. Desperate to complete his memoirs before his death so his family might have some financial security and he some redemption, Grant journeys back in time. He had once been the savior of the Union, the general to whom Lee surrendered at Appomattox, a twice-elected president who fought for the civil rights of Black Americans and against the rising Ku Klux Klan, a plain farmer-turned-business magnate who lost everything to a Wall Street swindler, a devoted husband to his wife Julia and loving father to four children. In this gorgeously rendered and moving novel, Grant rises from the page in all of his contradictions and foibles, his failures and triumphs.